Governance Quality and Information Asymmetry. Issue 2 (6th April 2015) - Elbadry, Ahmed; Gounopoulos, Dimitrios; Skinner, Frank
Abstract : This paper explores the relation between corporate governance and asymmetric information. We find that proxies for governance mechanisms that encourage the monitoring of managers are inversely related to proxies for asymmetric information. Specifically, greater board independence, board activeness and debt financing are significantly and inversely related to the degree of asymmetric information as reflected in bid‐ask spreads, volatility of share returns, normalised share trade volumes and market value of shares traded. This implies that corporate governance mechanisms that enhance managerial monitoring lead to improvements in the informational environment of the firm.